2022
DOI: 10.3390/jcm11144056
|View full text |Cite
|
Sign up to set email alerts
|

Use of Black-and-White Digital Filters to Optimize Visualization in Cataract Surgery

Abstract: Purpose: To evaluate the effect of a black-and-white (BW) filter on the optimization of visualization at each stage of cataract surgery. Methods: Prospective, single-center, single-surgeon, consecutive case series of 40 patients undergoing cataract surgery with BW filter. Surgical images and videos were recorded with and without the BW filter at each stage of cataract surgery. Contrast measurements of surgical images and subjective analysis of video sequences were performed. Results: The surgeons assessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Digital technology makes the use of color filters during surgery possible, resulting in better contrast and, thus, a clearer visualization of structures. Several studies have reported improvements in visualization with digital images for both cataract surgery and epiretinal membrane staining during surgery [9,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Digital technology makes the use of color filters during surgery possible, resulting in better contrast and, thus, a clearer visualization of structures. Several studies have reported improvements in visualization with digital images for both cataract surgery and epiretinal membrane staining during surgery [9,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Color saturation was slightly decreased digitally to improve contrast. It has been reported that decreases in color saturation can improve the delimitation of tissue contours in visualizations, facilitating internal limiting membrane peeling and enhancing visualization during cataract surgery [9,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 The black-and-white filter added in standard illumination optimized tissue visibility but also leaded to difficulties in nuclear sculpture and incision location. 13 We used the 3D-C approach to increase visualization performance during phacoemulsification. Both objective and subjective approaches are used to qualify the performance of the NGENUITY 3D visualization system in this study.…”
Section: Discussionmentioning
confidence: 99%
“…With this technology, digital filters can be applied in real time during surgery to increase contrast and improve the visualization of structures. Several studies have reported improvements in visualization with digital images for both cataract surgery and epiretinal membrane staining during surgery [ 14 , 15 ]. Here, we describe the feasibility of using digital visualization and its contribution to the enhancement of MP visualization and analysis in a prospective series of macular surgery interventions.…”
Section: Introductionmentioning
confidence: 99%